Committee on Transport Policy and Coordination Notes on Transpiration Policy (With Particular Reference To Road-Rail Coordination) in Some Foreign Countries - Planning Commission (Planning Commission, 1961)
The railways were for long the principal inland transport service in Australia, although there was some river traffic. The railway construction was undertaken to stimulate general development - to "open up" the country. As the use of motor vehicles for the carriage of passengers and goods developed, particularly in the. late twenties, the necessity to regulate, in the public interest, this form of transport was generally recognised.
Government of India Planning Commission
Government of India Planning Commission